E-learning Portal Success in higher education organizations: A multi-group comparison - Sanjoy Kumar Roy (Journal of Social, Humanity, and Education, 2023)
Purpose: This study provides an analytical framework based on the literature to evaluate the effectiveness of E-learning portals. The study aims to contrast the accessibility of e-learning portals from the perspectives of business and engineering students. Research methodology: Using convenience and snowball sampling methods with the help of Google polls, the data was acquired from 482 students, including engineering and business students. The study used a seven-point Likert-type questionnaire to gather data. The study employed PLS-SEM to do a multi-group analysis and examine group differences. Results: The results revealed user satisfaction predicts the system used for both models. Only e-service quality is the significant predictor of user satisfaction and the system used in the business model, but the system and information qualities are also predictors in the engineering model. Finally, the success of an e-learning portal is positively correlated with user satisfaction and system use. Limitations: This study consists of only a sample of 482 students. Future research may take into account using a bigger sample size. Additionally, this study mostly focused on how students perceived the efficacy of the e-learning portal while ignoring the viewpoints of the instructors and the institution, which may vary. Contribution: Higher administration in Bangladeshi educational institutions will find the study helpful in building policies and plans for the growth of e-learning portals. Novelty:  This work validates the DeLone and McLean Model in the context of Bangladeshi undergraduate students. The study shows how business and engineering students' access to e-learning portals varies.